Thermal conductivity-controlled Zn-doped MgO/Mg(OH)2 micro-structures for high-efficiency thermo-dynamic heat energy storage - Kim, Youngho; Lee, Jaeyeong; Kim, Noeul; Yu, Hak Ki (Journal of Asian Ceramic Societies, 2020)
Zn-doped MgO/Mg(OH)2 was used to increase thermal energy storage efficiency. Among general bulk materials, the thermal conductivity of those materials used for high-efficiency thermal energy storage should be high. In micro (or nano) structures, however, the lower the thermal conductivity, the heat can be more easily concentrated on the surface, enabling a thermodynamic reaction to store heat energy to be easily induced. Zn-doped MgO limits the vibration of the lattice and ultimately lowers the thermal conductivity. This reduced thermal conductivity increases the surface heat accumulation, and it was confirmed that dehydrogenation of Mg(OH)2 surfaces can occur rapidly, increasing the thermal energy storage efficiency.
Keywords: Bulk materials; Heat accumulation; Heat energy; High-efficiency; Zn-doped; thermal conductivity; Thermal energy storage; Zn-doped MgO (Mg1-xZnxO)